Czech workers reconsideration of work from home during COVID-19 - Beno, Michal; Krzova, Jaroslava; Cagánová, Dagmar (Journal of Eastern European and Central Asian Research (JEECAR), 2023)
Employers and employees are continuing to experiment with work from home patterns. During the COVID-19 pandemic, the “home office,” a practice begun to slow down the pandemic by decreasing physical contact, has become the new norm in Czechia. To fill a research gap in the new work-from-home (WFH) field, the authors of this paper were interested in conducting research to find out whether there are significant differences in Czech employees’ perception between working remotely and going back into the office. An online questionnaire with 150 respondents was designed to answer the research question and test seven hypotheses. There are significantly more employees working from home at their own request than there are working from home solely at the request of the company. Furthermore, employees with a separate office at home work there significantly more often than those without a separate office. The most common motivations for working from home are: absence of commuting (47.33%), flexibility (43.33%), and fewer interruptions (26%). The tolerance of working from home in Czechia does not seem to be able to withstand a downturn flexibility trend. In other words, the Czech workforce does not prefer working from home to become a fixture in the future.